Context-Dependent Acoustic Signals in the Four-Eyed Fir Bark Beetle, Polygraphus proximus (Coleoptera: Curculionidae: Scolytinae). Issue 1 (10th December 2018) - Kerchev, Ivan A
Abstract: Invasion of Polygraphus proximus (Blandford) has caused an extensive destruction in the aboriginal forest ecosystems of South Siberia. The goal of this study was to better understand the acoustic communication of P. proximus by analyzing the beetles' sound-production mechanisms and comparing sounds produced during different behaviors. Comparisons applied waveform analysis and quantitation of temporal parameters such as syllable, chirp duration, interchirp interval, number of tooth-strike per chirp, strike rate, and the duration of intervals between strikes. We recorded the acoustic signals of the bark beetle in three behavioral contexts: stress (handling), rivalry (male–male interactions), and courtship (male–female interactions). Acoustic signals produced during stress, rivalry behavior, and courtship chirps have very similar waveforms but are distinguishable according to temporal parameters (e.g., number of strikes in chirps and duration of intervals between them). During courtship, males produce two types of chirps. The first type was produced in all three contexts. The second chirp type was registered only in male–female interactions just before copulation. Precopulation signals produced by rubbing of the tibia against the elytral margin were registered for the first time in a bark beetle. The role of the precopulation signal was the clearest. The established modulations of signals in stress trials in comparison with the similar courtship and rivalry chirps are apparently due to effects of insect body movement against restraint. We hypothesize that the chirp temporal parameters in courtship and rivalry may be used by the sender to reveal his presence or physical characteristics to a receiver (female or rival male).